Iron and Copper Toxicity in Rat Liver: A Kinetic and Holistic Overview - Musacco Sebio, Rosario Natalia (2017)
Iron (Fe) and copper (Cu) overloads in rats showed a dose and time dependent metal accumulationin liver with its associated toxicity. The increased contents of the transition metals markedly enhanced the endogenous free-radical mediated processes of phospholipid peroxidation. Invivo liver chemiluminescence showed an increased production of 1 O2, and a consumption ofreduced glutathione (GSH), the main intracellular antioxidant. Results fit with a Haber-Weiss type molecular mechanism in which Fe or Cu and endogenously produced O2- and H2O2, yield HO radical that initiates free-radical mediated phospholipid peroxidation and protein oxidation.